Improving Communication in Nursing Homes Using Plan-Do-Study-Act Cycles of an SBAR Training Program. (February 2023) - Kay, Samantha; Unroe, Kathleen T.; Lieb, Kristi M.; Kaehr, Ellen W.; Blackburn, Justin; Stump, Timothy E.; Evans, Russell; Klepfer, Sarah; Carnahan, Jennifer L.
Background: Incomplete communication between staff and providers may cause adverse outcomes for nursing home residents. The Situation-Background-Assessment-Recommendation (SBAR) tool is designed to improve communication around changes in condition (CIC). An adapted SBAR was developed for the Centers for Medicare and Medicaid Services demonstration project, OPTIMISTIC, to increase its use during a resident CIC and to improve documentation. Methods: Four Plan-Do-Study-Act (PDSA) cycles to develop and refine successive protocol implementation of the OPTIMISTIC SBAR were deployed in four Indiana nursing homes. Use of SBAR, documentation quality, and participant surveys were assessed pre- and post-intervention implementation. Results: OPTIMISTIC SBAR use and documentation quality improved in three of the four buildings. Participants reported improved collaboration between nurses and providers after SBAR intervention. Conclusion: Successive PDSA cycles implementing changes in an OPTIMISTIC SBAR protocol for resident CIC led to an increase in SBAR use, improved documentation, and better collaboration between nursing staff and providers.